Sensory-spinal neuron co-culture platform enables analysis of sensory-driven spinal activation - Miyahara, Yuki; Shimba, Kenta; Kotani, Kiyoshi; Jimbo, Yasuhiko (Frontiers in Neuroscience, 2025)
BackgroundPain plays a crucial role in selecting behaviors essential for survival. Nociceptive stimuli are converted into neuronal signals by dorsal root ganglion (DRG) neurons and transmitted via the spinal cord to the brain, where pain is perceived. Chronic pain, characterized by prolonged nociceptive signaling, significantly reduces the quality of life. Specifically, nociplastic pain arises due to heightened spinal neuronal activity. However, the mechanisms underlying this persistent increase remain unclear, impeding the development of effective treatments. Therefore, the present study aimed to develop an experimental platform to investigate how sensory neuron signals increase spinal neuronal activity.MethodsWe developed a specialized microstructure enabling a separate culture of DRG and spinal neurons connected functionally by axons extending through microtunnels.ResultsImmunofluorescence staining confirmed precise spatial separation and robust neuronal network formation. Microstructures were integrated with high-density microelectrode arrays to facilitate electrophysiological recordings during co-culture. Optogenetic stimulation of DRG neurons significantly activate the spinal neurons, which are not active spontaneously, and increase synchronous activity by 11.8-fold in the spinal neuronal network. Notably, elevated spinal neuron activity persisted for at least 20 min after stimulation ceased, indicating a prolonged neuronal response.ConclusionThis novel co-culture system provides a powerful tool for elucidating the pathogenic mechanisms underlying chronic pain, potentially guiding future therapeutic strategies.